Oral Hyaluronic Acid Supplementation for the Treatment of Dry Eye Disease: A Pilot Study - Yeseul Kim; Chan Hee Moon; Bo-Yeon Kim; Sun Young Jang (Journal of Ophthalmology)
Purpose. To evaluate the clinical efficacy of oral hyaluronic acid (HA) in patients with dry eye disease (DED). Study Design. Prospective randomized controlled trial. Methods. This trial enrolled 54 subjects and they were randomized into the study or control group. The inclusion criteria were as follows: (1) >18 years of age; (2) distance best-corrected visual acuity ≥ 20/40 Snellen equivalent in each eye; (3) IOP ≤ 21 mmHg in both eyes; (4) ocular surface disease index (OSDI) score of ≥18 and <65; (5) <10 seconds of tear break up time (TBUT); (6) >5 corneal spots of corneal fluorescein staining (CFS); and (7) ≤ 10 mm/5 min of the Schirmer test. All subjects were treated with a topical HA, and the study group was supplemented with oral HA. OSDI, TBUT, CFS, and the Schirmer test were evaluated for ocular surface parameters. Results. 24 patients were assigned in the study group. Significant improvement of OSDI, TBUT, and CFS was observed at 1 month and 3 months after oral HA administration in the study group. At baseline and follow-up at 1 and 3 months, OSDI scores were 61.8 ± 16.2, 47.3 ± 11.6, and 42.3 ± 9.1, respectively (P<0.001). TBUT was improved after treatment for 1 month and 3 months (4.2 ± 1.1; P=0.005 and 4.7 ± 1.1; P<0.012). There were also statistically significant improvements in the CSF (1.8 ± 1.0, 0.8 ± 0.7; P<0.001) at baseline compared with those at 1 month. Conclusions. A combined supplement of both oral and topical HA more efficiently improves corneal epithelial wound healing and related symptoms than topical HA alone, in DED.